An index for assessing the quality of plant residues and evaluating their effects on soil and crop in the (sub) humid tropics - Tian, G.; Brussaard, Lijbert; Kang, B. (Elsevier, 1995)
An equation was developed for calculating a plant residue quality index (PRQI) in the (sub-)humid tropics using the C/N ratio and lignin and polyphenol concentration of plant residues. Among 18 plant species tested, there was a large variation in PRQI. The PRQI was correlated with the decomposition rate of plant residues, soil microclimate, soil fauna density and maize crop performance in the field. Soil moisture and termite density increased with decreases in PRQI, whereas decomposition rate constants of plant residues, soil temperature and ant density increased with increase in PRQI. Improvement in crop performance, such as grain yield, by plant residue mulching was lowest in the case of intermediate PRQI. It is concluded that PRQI can be used for selecting plant residues and projecting their agronomic value in the tropics.